Ingestible devices for oral delivery of biotherapeutics: A Mini Review - Akshay Khandke; Sanika Dhaybar; Avani Mandke; Ananya Joshi; Amol D. Gholap; Amarjitsing Rajput (Next Nanotechnology)
Bioactive macromolecules (like antibodies and peptides) are promising therapeutic agents for treating several diseases. However, oral administration of these macromolecules is challenging due to gastrointestinal (GI) tract degradation due to the harsh pH conditions, digestive enzymes, mucus layers and gastric acid. These barriers cause degradation affect the absorption and reduce the bioavailability of drugs. Thus, the bioavailability achieved by oral administration is less compared to parenteral administration. But parenteral administration of drugs causes reduced patient compliance, invasive and most painful. On the other hand, oral administration is non-invasive painless, but also results in higher patient compliance. Smart ingestible devices like microneedle devices, microrobots, magnetically triggered capsules, self-unfolding foils, smart pills, SOMA, LUMI, nano-straws and gastric auto-injectors can help resolve the issues related to oral delivery of bioactive agents and therapeutics. These devices overcome the GI tract barriers and successfully carry out the oral delivery of these drugs in the GI tract. This review explores how these smart ingestible devices can be an innovative alternative to the parenteral administration of bioactive macromolecules and biotherapeutics. It also covers the devices' functioning, mechanism, clinical stages and challenges in clinical transition. Our review article stands out in the current body of literature by comprehensively compiling all categories of ingestible devices for oral delivery, including the mechanism of drug release, monitoring, therapeutic systems and applications. This integrative approach is notably absent in previous review articles, which tend to focus on isolated aspects or specific types of devices. Furthermore, our article incorporates and analyzes the most recent advancements, offering a current, relevant, and more comprehensive overview than existing review articles by covering the latest literature.